1996
DOI: 10.1016/0029-7844(96)00055-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Staging and High Dose Rate Brachytherapy for Endometrial Cancer: Limiting External Radiotherapy to Node-Positive Tumors

Abstract: Surgical staging and high dose rate brachytherapy without external radiotherapy for stage I-IIIA endometrial cancer were associated with minimal morbidity and produced excellent survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 8 publications
0
47
0
1
Order By: Relevance
“…Especially, prospective studies with large patient numbers reported accuracy rates of frozen-section diagnosis for myometrial invasion from 95 to 97% [16,17], while accuracy rates of retrospective studies varied from 72 to 90%. We must admit that the comparison of retrospective studies with prospective studies does not claim to be conclusive, but, as a matter of fact, prospective studies are rare [14,16]. Despite the lower accuracy rate of frozen-section diagnosis for myometrial invasion in our patient collective, an optimal individualized treatment of our patients suffering from stage I endometrial adenocarcinoma was guaranteed, mainly because of our guideline to perform surgical staging including pelvic lymphadenectomy in moderately differentiated tumors with myometrial invasion, and to perform additional para-aortic lymphadenectomy in moderately differentiated tumors with myometrial invasion, and to perform additional para-aortic lymphadenectomy in poorly differentiated tumors and in all tumors with deep myometrial invasion (more than 50%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, prospective studies with large patient numbers reported accuracy rates of frozen-section diagnosis for myometrial invasion from 95 to 97% [16,17], while accuracy rates of retrospective studies varied from 72 to 90%. We must admit that the comparison of retrospective studies with prospective studies does not claim to be conclusive, but, as a matter of fact, prospective studies are rare [14,16]. Despite the lower accuracy rate of frozen-section diagnosis for myometrial invasion in our patient collective, an optimal individualized treatment of our patients suffering from stage I endometrial adenocarcinoma was guaranteed, mainly because of our guideline to perform surgical staging including pelvic lymphadenectomy in moderately differentiated tumors with myometrial invasion, and to perform additional para-aortic lymphadenectomy in moderately differentiated tumors with myometrial invasion, and to perform additional para-aortic lymphadenectomy in poorly differentiated tumors and in all tumors with deep myometrial invasion (more than 50%).…”
Section: Discussionmentioning
confidence: 99%
“…But in a recent prospective evaluation, the morbidity of complete lymphadenectomy in endometrial cancer was minimal, if surgical staging was performed by certified gynecologic oncologists [13]. In addition to excellent survival, Fanning et al [14,15] showed that complete lymphadenectomy in endometrial cancer patients served as the most important prognosticator, and allowed accurate tailoring of postoperative radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fanning et al [19] also reported no increase in risk with lymphadenectomy, although it should be noted that they reported an exceedingly low median blood loss of 25 cc's from lymphadenectomy.…”
Section: Morbidity Of Lymphadenectomymentioning
confidence: 89%
“…Centers with high level expertise may report complication rates that are lower than can be expected among practitioners in general. Furthermore, there is great variation in complication rates reported in the literature [17][18][19]. Secondly, many reported ''complications'' may be of little or no clinical consequence.…”
Section: Morbidity Of Lymphadenectomymentioning
confidence: 93%
“…Although a direct route of lymphatic spread from the corpus uteri to the para-aortic through the infundibulopelvic ligament has been suggested from anatomical studies 4 , direct metastases to the para-aortic LN is uncommon, ranging from 0 to 6% 20,21,24,[26][27][28][29][30] .…”
Section: Locations Of Lymph Node Metastasismentioning
confidence: 99%